Design of adaptive sliding mode controller for synchronization of chaos in system of Rossler in presence of uncertainty parameters - Nazari, Siroos; Kazemi, Sajjad; Mokhtavay, Hadis (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Many of the proposed approaches for nonlinear systems control are developed under the assumption that all involved parameters are known. However, the system uncertainties are always unavoidable and some system parameters cannot be exactly known in the most part of the cases. In this paper, a adaptive controlscheme is proposed to system is able to achieve the control objective regardless the parametric uncertainties of the model and the lack of a priori knowledge on the system. Also, is applied the adaptive sliding mode control for synchronization of chaos in system of Rossler in presence of unknown parameters. First, suppose that there are no parameter uncertainties in the system model. Then, this condition is removed while an adaptive sliding mode control system is designed. The advantages of obtaining such a motion are twofold: firstly the system behaves as a system of reduced order with respect to the original plant; and secondly the movement on the sliding surface of the system is insensitive to a particular kind of perturbation and model uncertainties.